PENERAPAN PP NO.71 TAHUN 2010 DALAM PELAPORAN AKUNTANSI BELANJA DINAS PEKERJAAN UMUM KOTA KOTAMOBAGU TAHUN ANGGARAN 2014 - Kiay Demak, Dedy Kurniawan; Sondakh, Jullie J.; Tangkuman, Steven (JURNAL RISET AKUNTANSI GOING CONCERN, 2015)
After the revision which takes about five years, Government Regulation in 2005 No.24, now is changed to be the Government Regulation in 2010 No.71 concerning Governmental Accounting Standards, also bring changes in standards and mechanisms in Government especially in expenditure statements. The aims of this research are to determine the form of presenting and reporting of expenditure accounting in Public Works Department in Kotamobagu City with the implementation of Government regulation 2010 No.71. This research uses the method of descriptive analysis. The results are in 2013 to 2014, the Public Works Department in Kotamobagu City has not yet applying the Government Regulation 2010 No.71 in presenting of expenditure reports, however it suits with the Government Regulation in 2005 No.24. The differences are placed in expenditure of transactions recording, also in financial statement. It is expected in the next year of budgets, Public Works Department is supposed to be fully guided by the regulation of Ministry of Home Affairs 2013 No.64, and also apply the Government Regulation 2010 No.71 in presenting the financial statement especially for expenditure.